Financial Education, Illegal Loans, Rural Msmes, Financial Literacy: Pengabdian - Satria Putra Utama; Muhammad Simba Sembiring; Afrizal; Raihan Hanasi; Maya Kasmita (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) in rural areas play a crucial role as the backbone of the domestic economy. However, limited financial literacy and difficult access to formal financial institutions often trap MSMEs in a vicious cycle of illegal online loans (illegal pinjol) and loan sharks. This community service activity aims to improve understanding of financial management and educate rural MSMEs about the fatal risks of illegal loans. The